The IMPLEMENTASI FATWA DSN MUI NO. 28 TERHADAP TRADING DENGAN MENGGUNAKAN FITUR SWAP FREE PADA BROKER FBS - Mochamad Mugni Labib; Muhajir, muhajir (Institut Agama Islam Darul Ulum Kandangan, 2021)
Currency buying and selling or better known as forex trading, is a business field that lures large profits with minimal effort. This is what attracts the Muslim community to get involved in this business. This thesis aims to analyze the swap free feature used by trading at the FBS broker, in which FBS claims that the swap free feature is considered sufficient to consider trading at an FBS broker in accordance with the provisions of the Shari'ah. The method used is the library research method. The data were analyzed from the Al-quran, Hadith, fiqh books, books, the internet, as well as the writings of classical and modern Islamic economics scholars. The aspect examined in this thesis is the swap free feature at the FBS broker, then collided with MUI DSN Fatwa No. 28 / DSN-MUI / III / 2002 to find out that trading with the FBS broker is in accordance with the shari'ah rules. The conclusion drawn from this research is that the swap free feature only deals with the interest or commission arising from an overnight open order so that traders do not get a discount or additional from the overnight order. The law of forex transactions at the FBS broker is not in accordance with the MUI DSN Fatwa Number 28 / DSN-MUI / III / 2002, because the trading system as a whole is still the same without activating this feature. Namely, such as taking advantage of currency exchange rate fluctuations, being able to take advantage of leverage / margin, and also carrying out a short selling strategy.